(untitled) (American Journal of Pedagogical and Educational Research, 2023)
The article reflects on the history of the development of mediata education and mediata education and the main aspects of the system of mastering and mediata education, the history and methodology of teaching mediata education. In addition, the main reasons for the consumption of media in digital media are given.